Cortical Microhemorrhages Cause Local Inflammation but Do Not Trigger Widespread Dendrite Degeneration - Rosidi, Nathanael L. (Public Library of Science, 2011)
Microhemorrhages are common in the aging brain, and their incidence is correlated with increased risk of neurodegenerative disease. Past work has shown that occlusion of individual cortical microvessels as well as large-scale hemorrhages can lead to degeneration of neurons and increased inflammation. Using two-photon excited fluorescence microscopy in anesthetized mice, we characterized the acute and chronic dynamics of vessel bleeding, tissue compression, blood flow change, neural degeneration, and inflammation following a microhemorrhage caused by rupturing a single penetrating arteriole with tightly-focused femtosecond laser pulses. We quantified the extravasation of red blood cells (RBCs) and blood plasma into the brain and determined that the bleeding was limited by clotting. The vascular bleeding formed a RBC-filled core that compressed the surrounding parenchymal tissue, but this compression was not sufficient to crush nearby brain capillaries, although blood flow speeds in these vessels was reduced by 20%. Imaging of cortical dendrites revealed no degeneration of the large-scale structure of the dendritic arbor up to 14 days after the microhemorrhage. Dendrites close to the RBC core were displaced by extravasating RBCs but began to relax back one day after the lesion. Finally, we observed a rapid inflammatory response characterized by morphology changes in microglia/macrophages up to 200 µm from the microhemorrhage as well as extension of cellular processes into the RBC core. This inflammation persisted over seven days. Taken together, our data suggest that a cortical microhemorrhage does not directly cause significant neural pathology but does trigger a sustained, local inflammatory response.